Why people prefer to be single: Sociosexuality, Dark Triad, and career focus effects. (October 2022) - Apostolou, Menelaos; Patsiarika, Georgia
Abstract: Although most people look for and eventually find long-term mates, many opt out from the mating market, preferring to be single instead. The current research aimed to identify some of the factors which are likely to be associated with increased likelihood to be voluntarily single. More specifically, we examined the effects of sociosexuality, Dark Triad, and career focus on relationships status. Our results indicated that men and women who tended toward unrestricted sociosexuality and who scored higher in the Dark Triad, were more likely to prefer to be single than in an intimate relationship. We also found a three-way interaction between career focus, sex and age. In particular, higher career focus was associated with higher probability to be voluntarily single than in an intimate relationship, among younger than older women. The implications of these findings for understanding singlehood were further discussed. Highlights: Finds that sociosexuality predicts voluntary singlehood. Finds that the Dark Triad predicts voluntary singlehood. Finds a three-way interaction between career focus, sex and age on singlehood status